Pertimbangan Anestesi pada Pasien dengan Myeloradiculopathy pada Tingkat Vertebra Th2-Th4 Menjalani Anterior Cervicosternotomy - Nadya, Siti Fairuz; Fuadi, Iwan (ACTA Medical Health Sciences, 2023)
Myeloradiculopathy, a condition that involves the spinal cord and spinal nerve roots, is the major cause of disability patients. Most patients with myeloradiculopathy receive surgical intervention with the aim of removing the underlying compression injury from the nerve, decompressing the cord, and moving it without friction or further damage. Surgery on the spine and spinal cord has broadened its scope in recent years. The anterior approach is a challenging procedure given the various vascular, osseous, nervous, and articular structures that prevent adequate exposure and the potential damage to anesthetists. Our objective was to evaluate the pre-operative analysis, maintenance during intra-operative care, and post-operative care in patients with myeloradiculopathy undergoing posterior stabilization surgery with an anterior approach (cervicosternotomy). A 23-year-old woman was diagnosed with Myeloradiculopathy at Th2 Vertebrae Level due to space-occupying extradural lesion at Th2-Th4 vertebral level with pathological fracture at Thoracal Th2 et Th7 et Th10 due to suspected spondylitis tuberculosis with paravertebral abscess, with ASA I (Physical Status Classification System). The patient was then treated with laminectomy debridement, abscess drainage, and posterior stabilization through a cervicothoracic spine surgery with an anterior approach. The patient received the preoperative assessment, intraoperative maintenance, and postoperative evaluations, which  are very important to ensure a good outcome of the cervicosternotomy with an anterior approach. DOI : 10.35990/amhs.v2n2.p88-95 REFERENCE Cook CE, Cook AE. Cervical Myelopathy and Radiculopathy. In: Elsevier Ltd.; 2011. doi:10.1016/B978-0-7020-3528-9.00009-1 Stanley B. An introduction to anaesthesia for neurosurgery. Updat Anaesth. 2007;(23):43–8. Nagpal A. No Title. PM&R Knowledge NOW. Fuentes S, Malikov S, Blondel B, Métellus P, Dufour H, Grisoli F. Cervicosternotomy as an anterior approach to the upper thoracic and cervicothoracic spinal junction: Technical note. J Neurosurg Spine. 2010;12(2):160–4. doi:10.3171/2009.9.SPINE09471 Khanna P, Sarkar S, Garg B. Anesthetic considerations in spine surgery: What orthopaedic surgeon should know! J Clin Orthop Trauma. 2020;11(5):742–8. doi:10.1016/j.jcot.2020.05.005 Raw DA, Beattie JK, Hunter JM. Anaesthesia for spinal surgery in adults. Br J Anaesth. 2003;91(6):886–904. doi:10.1093/bja/aeg253 Prough DS, Svensén CH. Perioperative fluid management. Anesth Analg. 2006;4(Suppl):84–91. doi:10.5492/wjccm.v4.i3.192 Bao FP, Zhang HG, Zhu SM. Anesthetic considerations for patients with acute cervical spinal cord injury. Neural Regen Res. 2017;12(3):499–504. doi:10.4103/1673-5374.202916 Lall RR, Hauptman JS, Munoz C, et al. Intraoperative neurophysiological monitoring in spine surgery: Indications, efficacy, and role of the preoperative checklist. Neurosurg Focus. 2012;33(5):1–10. doi:10.3171/2012.9.FOCUS12235 Kursumovic E, Arrowsmith JE. Reviews of Educational Material. Anesthesiology. 2017;127(4):731. doi:10.1097/aln.0000000000001745 Li ZJ, Fu X, Xing D, Zhang HF, Zang JC, Ma XL. Is tranexamic acid effective and safe in spinal surgery? A meta-analysis of randomized controlled trials. Eur Spine J. 2013;22(9):1950–7. doi:10.1007/s00586-013-2774-9 Cottrell J, Patel P. Cottrell and Patel’s Neuroanesthesia. 6th ed. 2016. Available from: https://shop.elsevier.com/books/cottrell-and-patels-neuroanesthesia/cottrell/978-0-323-35944-3 Cunha PD, Barbosa TP, Correia G, et al. The ideal patient positioning in spine surgery: a preventive strategy. EFORT Open Rev. 2023;8(2):63–72. doi:10.1530/EOR-22-0135 Luo J, Min S. Postoperative pain management in the postanesthesia care unit: An update. J Pain Res. 2017;10:2687–98. doi:10.2147/JPR.S142889 Prabhakar NK, Chadwick AL, Nwaneshiudu C, et al. Management of postoperative pain in patients following spine surgery: A narrative review. Int J Gen Med. 2022;15(May):4535–49. doi:10.2147/IJGM.S292698